ANALYSIS OF THE SCIENTIFIC RESEARCH CONDUCTED IN THE DIRECTION OF ENERGY SUPPLY OF ELECTRICAL CONVECTORS IN SPECIAL SMART SHOES THAT PROTECT THE FOOT PAW FROM THE INFLUENCE OF AN UNFAIR ENVIRONMENT - Associate Professor Ilhamova M. U.; Makhmudov Kh. Y. (Journal Park Publishing, 2023)
The article analyzes the scientific research and received patents on the cold climate protection of the paws, the energy supply of special heating shoes.
Keywords: Special shoes, electric generator, walking mechanism, cartogram, renewable energy.